Persepsi Kepuasan Konsumen terhadap Produk Kopi di UD. Tyyana Coffee - Sutan Pulungan; Novita Aswan; Siagian, Yudinar Ratnasari (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to analyze consumer satisfaction perceptions towards UD. Tyyana Coffee in Aek Sabaon Village, Tapanuli Selatan, conducted in May 2024 using accidental sampling and quantitative data analysis. Consumer satisfaction is measured based on loyalty, location, service, and coffee taste. The results show that customer loyalty falls into the "Satisfied" category with an average score of 3.60. The indicator of purchase frequency received the highest score (3.78), while repeat purchase frequency had the lowest (3.43), indicating opportunities for increasing loyalty. Regarding location, comfort received the highest score (4.53), but strategic location scored the lowest (4.04). Service was rated with an average score of 4.28, with friendliness as the highest aspect (4.30). Coffee taste showed the richness of coffee as the highest indicator (4.35), while flavor received the lowest score (4.05). Overall, consumers are satisfied with various aspects offered by UD. Tyyana Coffee, from a comfortable location and friendly service to its unique coffee taste.